Evaluation of Job Stress and Burnout Among Anesthesiologists Working in Academic Institutions in 2 Major Cities in Pakistan - Khan, Fauzia A.; Shamim, Mubashir H.; Ali, Liaqat; Taqi, Arshad (Anesthesia and analgesia, 2019)
Work stress is an integral part of anesthetic practice and has been a subject of many studies. Persistent stress can lead to burnout. There is limited published literature from lower- and middle-income countries where job stressors may be different from high-income countries. The aim of this study was to find out the level of burnout in a cohort of anesthesiologists working in academic institutions in 2 major cities of Pakistan, a low middle income country. We conducted an anonymous survey based on the Maslach Burnout Inventory scale with 3 major componentsemotional exhaustion; depersonalization; and burnout in personal achievement. The demographic and other work-related details were collected in a standardized manner. Our response rate was 74.5%. Seventy-seven percent of the participants were residents and 23% consultants. Gender distribution was 66.9% males and 33.1% females. Thirty-nine percent (95% CI, 34.8%–44.1%) showed moderate- to high-level emotional exhaustion, 68.4% (95% CI, 63.9%–72.7%) showed a moderate to high level of depersonalization, and 50.3% (95% CI, 45.6%–55.07%) showed a moderate to high level of burnout in personal achievements. On multivariable analysis, anesthesia not being the primary career choice was significantly associated with all 3-dimensional scales for the whole cohort. Factors significantly associated with emotional exhaustion were Lahore as city of work, >2 nights on call per week, and >40 h/wk work inside the operating room. Depersonalization burnout was again associated with Lahore as city of work, >40 h/wk work inside the operating room, and personal achievement burnout with >2 on-call nights per week. No association was observed for gender, marital status, or having children. In conclusion, a high rate of burnout was identified in anesthesiologists working in 2 major cities in Pakistan. Some new associated factors such as initial choice of specialty and city of work were highlighted. Based on these findings, preventive and coping strategies need to be introduced at institutional and national levels.